Assessing the causal role of hypertension on left atrial and left ventricular structure and function: A two-sample Mendelian randomization study - Sun, Yancui; Zhang, Ying; Xu, Nan; Bi, Cheng; Liu, Xiaojie; Song, Wei; Jiang, Yinong (Frontiers in Cardiovascular Medicine, 2022)
Aim: The aim of this study was to investigate whether hypertension may be causally linked to left atrial (LA) and left ventricular (LV) structure and function. Methods and results: We performed a two-Mendelian, randomization (MR) analysis implementing the results from the FinnGen large-scale, genome-wide association study for hypertension (N = 218,754), and LV (N = 16,923) and LA studies (N = 35,648) by the UK Biobank to identify genetic instruments. The MR analysis was implemented using an inverse-variance weighted approach. We identified a positive potential causal relationship between hypertension and indices for the LA maximum (LAmax with causal estimates of 0.126 [95% CI, (0.093–0.160)]); LA minimum (LAmin with causal estimates of 0.122 [95% CI, (0.089–0.156)]); LV function (causal estimates are LV end-diastolic volume (LVEDV), 0.078 [95% CI, (0.003–0.153)]; LV end-systolic volume (LVESV), 0.102 [95% CI, (0.030–0.173)]; LV mass (LVM), 0.171 [95% CI, (0.108–0.233)]; and LV mass to end-diastolic volume ratio (LVMVR at 0.098 [95% CI, (0.048–0.149)], respectively), which was directionally concordant with other robust MR methods. Other than this, we observed a significantly negative causal relationship between hypertension and the LA active emptying fraction (LAAEF), the LA passive emptying fraction (LAPEF) and the LA total emptying fraction (LATEF). Conclusions: Our genetic analyses demonstrated a potential causal relationship between hypertension and the left atrium and left ventricle’s structures and functions.